Stereotip Gender Dalam Profesi Tukang Ojek Online - Putri Cahya Sufiyah; Martinus Legowo (Universitas Merdeka Madiun, 2023)
In the world of work, the physical differences between men and women make the roles accepted by both of them are not the same. In society, this will always be associated with the phenomenon of gender stereotypes. Online motorcycle taxi drivers are one of the professions that are often used by most people. The ojol profession has a strong impression on men and is even considered unsuitable for women. This study aims to reveal how gender stereotypes are in the online motorcycle taxi driver profession. This method emphasizes more on descriptive research and more emphasis on detailed information analysis. The data analysis technique used is Miles and Huberman's data analysis. The data used is secondary data. Secondary data comes from literature sources such as journals, articles, theses, books, websites and other supporting sources. The results of the study show that in the online motorcycle taxi driver profession, gender stereotypes are found which have three forms, namely: first, the presence of a masculine identity and the distance from a feminine impression makes most women reluctant to become motorcycle taxi drivers. Second, online motorcycle taxi drivers are field work so they are considered difficult for women. Third, the ojol profession is seen as a high-risk job because of the many challenges that must be faced so that it is suitable for men. First, the existence of a masculine identity and distance from the feminine impression makes most women reluctant to become motorcycle taxi drivers. Second, online motorcycle taxi drivers are field work so they are considered difficult for women. Third, the ojol profession is seen as a high-risk job because of the many challenges that must be faced so that it is suitable for men. First, the existence of a masculine identity and distance from the feminine impression makes most women reluctant to become motorcycle taxi drivers. Second, online motorcycle taxi drivers are field work so they are considered difficult for women. Third, the ojol profession is seen as a high-risk job because of the many challenges that must be faced so that it is suitable for men.